Effect of Different Salting Treatments on Salted Egg’s Sensory Properties - william maramis; audrey guritno; nathanael davidson; evelyn djiuardi; niken taufiqurrahmi listyorini (Liaison Journal of Engineering, 2022)
Salted egg is one of the traditional and popular preserved egg products. Therefore, this study aims to observe the characteristics change of salted chicken eggs at different methods (dry and wet) and different salt concentrations (20% and 30%) with two different durations, namely 16 days and 21 days. The results of this salted egg experiment were also compared with salted commercial and hedonic tests. Duo-trio tests and triangle tests were also carried out. Sensory analysis was also carried out in this experiment by appointing five panelists. The hedonic test showed that most of the panellists chose salted eggs made by the wet method for 16 days with a salt concentration of 20%. Meanwhile, from the duo-trio test, all panelists chosen eggs were made using the wet method for 16 days with a salt concentration of 20%. The results on the triangle show that all panellists chose salted eggs were made using the wet method for 21 days with a salt concentration of 20%.Keyword: Salted Egg, Salted Commercial, Hedonic Tests, Sensory Analysis, Salt Concentration